Relational Supply Contracts Optimal Concessions in Return Policies for Continuous Quality Improvements - Höhn, Michaela Isabel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Supply relations are often governed by so-called relational contracts. These are informal agreements sustained by the value of future cooperation. Although relational contracts persist in practice, research on these types of contracts is only emerging in Operations and Supply Chain Management. This book studies a two-firm supply chain, where repeated transactions via well-established supply contracts and continued quality-improvement efforts are governed by a relational contract. We are able to characterize an optimal relational contract, i.e., to develop policies for supplier and buyer that structure investments in quality and flexibility in a way that no other self-enforcing contract generates higher expected joint surplus. A second goal is to compare the performance of different returns mechanisms in the context of relational contracting (quantity flexibility and buy-back contracts). Industry studies motivate the presented model.
Literature Review on Supply Chain Contracts -- Relational Contracts -- Relational Contracts and Optimal Quantity Flexibility -- Relational Contracts and Optimal Buy-Back Price -- QF vs. Buy-Back Contract in Buyer-Supplier Relationships -- Case Study: Supplier Relationship Management at Volkswagen Group -- Conclusion and Outlook.
Keywords: Industrial procurement; Operations research; Decision making; Economic theory; Mathematical optimization; Procurement; Operations Research/Decision Theory; Economic Theory/Quantitative Economics/Mathematical Methods; Optimization